P-120 LAPAROSCOPIC REPAIR OF INCISIONAL HERNIA USING A NON-ABSORBABLE TRANSPARENT COMPOSITE PROSTHESIS TOTALLY IN POLYPROPYLENE - OUR EXPERIENCE. (13th October 2022) - Pecic, V; Pavlovic, A; Todorovic, A; Bogdanovic, D; Dimitrijevic, M; Bekic, M; Rancic, L; Rosati, S; Balestra, G; Jovanovic, B
Abstract: Introduction: Incisional ventral hernia is one of the most common surgical complications after laparotomy. The aim of this retrospective observational study is an evaluation of clinical outcomes after laparoscopic repair of incisional hernias with a non-absorbable and transparent composite prosthesis composed of a macro-porous monofilament polypropylene mesh and a transparent polypropylene film. Materials and Methods: 63 patients, from January 2016 to December 2021, were treated for incisional hernia at Center of minimal invasive surgery Nis, Serbia. The mesh was always positioned intraperitoneally after closing the defects and fixed with absorbable tacks and non-absorbable suture. Results: In the considered cohort (54% female and 46% male) the median age and BMI were 54 years (range: 39–68) and 25, 1 kg/m 2 (range: 21.5–30.3), respectively. Concerning hernia position, 93.7% of the hernias were medial, 4.8% lumbar and 1.6% medio-lumbar. According to EHS classification, 58.7% of the hernias were W1, 36.5% W2 and 12.7% W3. The average duration of hospitalization was 2 days. The rate of early post-operative complications was 6.3%, including 1 seroma (1.6%) and 3 patients reporting pain (4.8%). At a median follow up of 48 months (range: 6–60) we registered 2 cases of hernia recurrency (3.2%, both at 36 months follow-up) and 1 case of bowel obstruction (1.6%). All the considered variables did not result statistically significative in relation to post-operative complications. Conclusion: Our clinical experience showed that intraperitoneal treatment of incisional hernia using a transparent composite prosthesis. The minimally invasive procedure allows a fast postoperative recovery and a consequent low economical cost.